2010
DOI: 10.1007/s00239-010-9335-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of Regulatory Genes in Spruces from Different Species and Continents: Heterogeneous Patterns of Linkage Disequilibrium and Selection but Correlated Recent Demographic Changes

Abstract: Genes involved in transcription regulation may represent valuable targets in association genetics studies because of their key roles in plant development and potential selection at the molecular level. Selection and demographic signatures at the sequence level were investigated for five regulatory genes belonging to the knox-I family (KN1, KN2, KN3, KN4) and the HD-Zip III family (HB-3) in three Picea species affected by post-glacial recolonization in North America and Europe. To disentangle neutral and select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 94 publications
9
59
1
Order By: Relevance
“…Weak population structure in white spruce from Québec has been reported in several studies using neutral genetic markers (Jaramillo-Correa et al, 2001;Namroud et al, 2008Namroud et al, , 2010 and was expected based on our previous analysis of a subset of the present discovery population . As a cautionary measure, we used the multidimensional scaling coefficients as population covariates for the GS analyses to control for any potential bias in prediction accuracy that could be brought about by such a population structure.…”
Section: Population Structuresupporting
confidence: 83%
See 2 more Smart Citations
“…Weak population structure in white spruce from Québec has been reported in several studies using neutral genetic markers (Jaramillo-Correa et al, 2001;Namroud et al, 2008Namroud et al, , 2010 and was expected based on our previous analysis of a subset of the present discovery population . As a cautionary measure, we used the multidimensional scaling coefficients as population covariates for the GS analyses to control for any potential bias in prediction accuracy that could be brought about by such a population structure.…”
Section: Population Structuresupporting
confidence: 83%
“…A population structure analysis was used to assess whether there were differences in allele frequencies among unobserved ancestral populations that could bias prediction accuracy estimates. Given the results obtained in previous studies conducted in the same area (JaramilloCorrea et al, 2001;Namroud et al, 2008Namroud et al, , 2010Beaulieu et al, 2011), we were expecting a weak or no population differentiation from SNPs. We used all available SNPs (m ¼ 6385) in multidimensional scaling and principal component analysis (Price et al, 2006) to estimate population covariates for each individual.…”
Section: Snp Genotypingmentioning
confidence: 71%
See 1 more Smart Citation
“…This corresponds to a scenario where gene flow is reduced among ecologically distant populations at loci directly involved in local adaptation or at closely linked loci, while there are no selective constraints on gene flow among environments for the rest of the genome (Barton, 2000; Gavrilets & Vose, 2005; Wu, 2001). This result is not surprising considering the rapid decay of linkage disequilibrium in large outcrossing populations of conifers (Namroud, Guillet‐Claude, Mackay, Isabel, & Bousquet, 2010) and the high levels of gene flow across the range of P. strobus (Mehes, Nkongolo, & Michael, 2009; Nadeau et al., 2015), which should uniformize among‐population genetic variation at neutral loci. Provenance trial studies have previously found moderate among‐population genetic variation for adaptive traits in P. strobus (e.g., height growth, bud phenology, cold hardiness; Li, Beaulieu, Daoust, & Plourde, 1997; Joyce & Sinclair, 2002; Lu, Joyce, & Sinclair, 2003a,b).…”
Section: Discussionmentioning
confidence: 94%
“…In similar comparisons made between Picea mariana and P. glauca (divergence time >10 MYA), Prunier, Laroche, Beaulieu, and Bousquet (2011) found more adaptive similarities at the gene family level (paralogs) than at the gene level (orthologs). The redundancy of functions among recently duplicated genes in conifers could have offered the possibility for selection to act on paralogous genes in different species (Namroud et al., 2010). In distantly related P. glauca and Pinus contorta (divergence time ~140 MYA), an exome‐wide study detected 47 genes (~10–18% of top candidate genes) with convergent signatures of local adaptation to low temperatures (Yeaman et al., 2016).…”
Section: Discussionmentioning
confidence: 99%